Implementasi Pendekatan Pembelajaran Interdisipliner Berbasis Literasi Digital dalam Mata Pelajaran Pendidikan Agama Islam di SD Negeri Palasari Kecamatan Sukabumi - Al Hadad, Moh. Alawi Al Hadad; Nugraha, Mulyawan Safwandy (CV. Berkah Cakrawala Inspirasi, 2026)
This study examines the implementation of an interdisciplinary learning approach based on digital literacy in Islamic Religious Education (IRE) at SD Negeri Palasari, Sukabumi Regency. The research is grounded in the growing need to enhance the quality and relevance of Islamic education in response to digital transformation and the demands of 21st-century learning. Employing a qualitative case study design, data were collected through classroom observations, in-depth interviews with teachers and school stakeholders, and document analysis of lesson plans and learning materials. The findings reveal that interdisciplinary learning supported by digital literacy enables IRE instruction to become more contextual, integrative, and meaningful by connecting religious concepts with other disciplines and real-life situations. The study also identifies key supporting factors, including teachers’ pedagogical competence, institutional support, and access to basic digital resources, alongside inhibiting factors such as limited instructional time and uneven digital literacy skills among educators. The results contribute to the development of an interdisciplinary framework for Islamic education at the primary level and highlight the potential of digital literacy as a strategic component in strengthening holistic and value-based learning.